Competition Policy and Government Intervention in Developing Countries: An Examination of Japanese Economic Development - Hiroshi Iyori (Washington University Global Studies Law Review, 2002)
This Article will discuss these two perspectives by first introducing the Japanese experiences in government intervention and competition policy, and then recommending what the competition policy should be in the Asia-Pacific Economic Cooperation (APEC) community. This analysis will divide government control into two aspects: intervention for forming and maintaining free markets and competition (“A-type” intervention) and intervention for controlling free markets and competition (“B-type” intervention).
Keywords: APEC; Economic development; Japan; Government intervention; History - Japan